Typing of Bovine Viral Diarrhea Viruses Directly from Blood of Persistently Infected Cattle by Multiplex PCR - Gilbert, S. A. (American Society for Microbiology, 1999)
A nested multiplex PCR was developed for genotyping of bovine viral diarrhea viruses (BVDVs). The assay could detect as little as 3 50% tissue culture infective doses of BVDV per ml and typed 42 out of 42 cell culture isolates. BVDV was also successfully typed, with or without RNA extraction, from all 27 whole-blood samples examined from 22 carriers or probable carriers and 5 experimentally infected cattle.